The kinetochore protein, CENPF, is mutated in human ciliopathy and microcephaly phenotypes. Issue 3 (6th January 2015) - Waters, Aoife M; Asfahani, Rowan; Carroll, Paula; Bicknell, Louise; Lescai, Francesco; Bright, Alison; Chanudet, Estelle; Brooks, Anthony; Christou-Savina, Sonja; Osman, Guled; Walsh, Patrick; Bacchelli, Chiara; et al.
Abstract : Background: Mutations in microtubule-regulating genes are associated with disorders of neuronal migration and microcephaly. Regulation of centriole length has been shown to underlie the pathogenesis of certain ciliopathy phenotypes. Using a next-generation sequencing approach, we identified mutations in a novel centriolar disease gene in a kindred with an embryonic lethal ciliopathy phenotype and in a patient with primary microcephaly. Methods and results: Whole exome sequencing data from a non-consanguineous Caucasian kindred exhibiting mid-gestation lethality and ciliopathic malformations revealed two novel non-synonymous variants in CENPF, a microtubule-regulating gene. All four affected fetuses showed segregation for two mutated alleles [IVS5-2A>C, predicted to abolish the consensus splice-acceptor site from exon 6; c.1744G>T, p.E582X]. In a second unrelated patient exhibiting microcephaly, we identified two CENPF mutations [c.1744G>T, p.E582X; c.8692 C>T, p.R2898X] by whole exome sequencing. We found that CENP-F colocalised with Ninein at the subdistal appendages of the mother centriole in mouse inner medullary collecting duct cells. Intraflagellar transport protein-88 (IFT-88) colocalised with CENP-F along the ciliary axonemes of renal epithelial cells in age-matched control human fetuses but did not in truncated cilia of mutant CENPF kidneys. Pairwise co-immunoprecipitation assays of mitotic and serum-starved HEKT293 cells confirmed that IFT88 precipitates with endogenous CENP-F. Conclusions: Our data identify CENPF as a new centriolar disease gene implicated in severe human ciliopathy and microcephaly related phenotypes. CENP-F has a novel putative function in ciliogenesis and cortical neurogenesis.